Phase Transitions and Damage Spreading in a Nonequilibrium Lattice Gas Model with Mixed Dynamic Rules - Rubio Puzzo, Maria Leticia (2015)
Phase transitions and damage spreading for a lattice gas model with mixed  driven lattice gas (DLG)-Glauber dynamics are studied by means of Monte Carlo simulations. In order to control the number of sites updated according to the nonconservative Glauber dynamics, a parameter p ǫ[0, 1] is defined. In this way, for p = 0 the system corresponds to the DLG model with biased Kawasaki conservative dynamics, while for p = 1 it corresponds to the Ising model with Glauber dynamics. The results obtained show that the introduction of nonconservative dynamics dramatically affects the behavior of the DLG model, leading to the existence of Ising-like phase transitions from fully occupied to disordered states. The short-time dynamics results suggest that this transition is second order for values of p = 0.1 and p > 0.6 and first-order for 0.1 < p ≤ 0.6. On the other hand, damage always spreads within the investigated temperature range and reaches a saturation value Dsat that depends on the system size, the temperature, and p. The value of Dsat in the thermodynamic limit is estimated by performing a finite-size analysis. For p < 0.6 the results show a change in the behavior of Dsat with temperature, similar to those reported for the pure (p = 0) DLG model. However, for p ≥ 0.6 the data remind us of the Ising (p = 1) curves. In each case,a damage temperature TD(p) can be defined as the value where either Dsat  reaches a maximum or it becomes nonzero. This temperature is, within error bars, similar to the reported values of the temperatures that characterize the mentioned phase transitions.